Retirement instruments and their distribution channels. - Ong, Cheow Chong. (2008)
Our study will be based on the Singapore context. More has to be done to help people plan for retirement. First, we hope to find out about the relationship between demographics and instruments used by them. Secondly, we hope to find out about people’s perception about the best distribution channels for promoting and purchasing retirement instruments.